‘Hypothesis non-fingo’ resolved with ‘Gill’s Electronic Theory of Magnetism 1964’ - Gill, Avtar S. (Newest Updates in Physical Science Research Vol. 11, 2021)
Applying Gill’s electronic theory of magnetism 1964 to planet Earth and relating it to the electron dependant negative force (-e) and the proton dependant positive force (+e) of atoms of any object close to the surface of the Earth, it will be explained mathematically how objects close to the Earth fall towards the Earth with a combination of these two forces. In the northern and southern magnetic hemispheres of the Earth, equations based on known physics laws are offered for objects falling towards the Earth. Dot-product vector equations will explain why a pendulum will accelerate least at the equator and this lateral acceleration keeps on increasing as we move the same pendulum from the equator towards the magnetic poles of the Earth as has been seen experimentally. As the object O gains height above the surface of the Earth, the two negative and positive extra-terrestrial forces become effective and O starts losing weight with increasing height. At a certain greater height above the Earth where the two negative and positive forces from the Earth balance with the two negative and positive extra-terrestrial forces, the object O will start behaving as a satellite. The bigger object O will become a satellite at a greater height. A brief discussion at the end on why this presentation is more accurate as compared to Sir Isaac Newton’s universal law of gravitation which resulted in the incorrect third force concept of gravity in 1687 in Physics. As the asymmetry between the magnetic force and the electrical forces is resolved with Gill’s electronic theory of magnetism 1964, Albert Einstein’s ‘Special Relativity theory 1905’ which was presented to deal with the asymmetry issue becomes unnecessary along with his ‘General Relativity theory 1916’ where he tries to justify the gravitational force.